An Empirical Analysis of China's Equilibrium Exchange Rate and Misalignment of the RMB - Zhu, Lin (2012)
As economic globalization develops in depth, the exchange rate as an important means of macroeconomic control and economic leverage has played a critical role in the economic development in China. Moreover, the real exchange rate can affect the competitiveness of a country’s economy. In fact, a large number of scholars claim that a country should maintain the real exchange rate at its “equilibrium level” in order to keep a steady growth of the economy. Thus, many studies have emphasized on estimating the “equilibrium” real exchange rate of the RMB. And then, people can use the equilibrium real exchange rate to calculate the misalignment of the RMB real effective exchange rate. This paper follows the empirical analysis and applies the time span from 1994 to 2011 with annual data. Furthermore, this paper chooses the behavioural equilibrium exchange rate (BEER) model and classifies the terms of trade, the degree of openness of economy, government consumption, net foreign assets, productivity and money supply as the explanatory variables of the RMB equilibrium exchange rate to re-estimate the RMB equilibrium real exchange rate (ERER) by using the Johansen co-integration method and vector error correction model (VECM). Then, after get the ERER of the RMB, the extent of misalignment of the RMB exchange rate can be calculated. As a consequence, the figures lead us to the conclusion that from 1994 to 2007 and after 2011, the percentage of misalignment is above zero and seemly to say that the RMB exchange rate is overvalued during these time period. While between 2007 and 2010, the percentage of misalignment is below zero, and hence to conclude that the RMB exchange rate is undervalued during this period. Moreover, due to the analysis from the international perspective, we conclude that the RMB is not undervalued.